Influenza: theatre of glowing darkness- Kristine Roepstorff/ Danish Pavilion : 57th International Art Exhibition- La Biennale di Venezia 2017 - Angiama, Sepake (author); Bauer, Ute Meta (author); Ellis, Patricia (editor); Ovesen, Solvej Helweg (author); Rosenberg, Angela (author) (Danish Arts Foundation, 2017)
Theatre of glowing darkness is the title of Roepstorff's theatre production, which is central to the exhibition; its values underpin the entire show, which is a fully immersive environmental experience that explores darkness as a condition of healing and reconciliation, an integral part of the natural cycle of death and rebirth. In Roepstorff's mystical darkness, form dissolves, unity is restored, and we become empowered to dream.
CONTENTS: -- 1. About the Title -- 2. About the Consortium: Sepake Angiama, Ute Meta Bauer, Solvej helweg Ovesen, Angela Rosenberg -- 3. About the Pavilion and Garden -- 4. About theatre of glowing darkness -- 5. About Renaissance of the Night -- 6. On darkness, transparency and fragility by Angela Rosenberg -- 7. of glass -- 8. influenza -- 9. the dark river: film noir, depression and I -- 10. midwife mary -- 11. oblivion -- 12. A voice, a small voice by Sepake Angiama -- 13. the architecture of intimacy- in search of dark spaces by Solvej Helweg Ovesen -- 14. In the world unseen by Ute Meta Bauer
English; Italian
Keywords: N4390-5098 Visual Arts- Exhibitions; Pavilion catalog; Denmark